ANALISIS KESESUAIAN IKLIM UNTUK PENGEMBANGAN CENDANA (Santalum album L.) DI NUSA TENGGARA TIMUR - Rizaldi Boer; Tania June (BERITA BIOLOGI, 2001)
Land suitability analysis method is introduced for sandalwood (Santalum album L.) in Nusa Tenggara Timur. It includes analysis on its (I) agro ecological suitability based on crop requirement for climate and soil characteristic, (2) ecological suitability, and (3) social-economic requirement for sustainable and profitable production. Approach to these three components is conducted through desk study/survey and on site research. All information collected and analyzed is combined together in GIS (Geographical Information System) for further use.